Schirley P. França and the artesania of caring: Memories of a mother puppeteer of many children and puppets. (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
Shirley P. França works in the field of Performing Arts, Education, Literature andPopular Culture as an actress, educator, puppetter, storyteller and brincante. Matriarch of thefamily troupe Companhia Carroça de Mamulengos has traveled Brazil for 43 years promoting Artand Culture. This article presents an interview with Schirley P. França, addressing her trajectoryand experiences along the journey as an artist and mother, since childhood and the influence ofwomen in the family, going through the theatrical adventures of adolescence, the long years withthe Carroça de Mamulengos and the dream of graduating from university, which was achieved in2020.